Автоматная модель поведения тиристорного ключа - Алымов, О.П.; Кулешов, Ю.Е.; Головко, А.А. (Технічна електродинаміка, 2012)
The automatic model of behavior thyristor a switch which all components are set obviously is synthesized, and allowing to formalize logic synthesis of a digital control system of the electric converter with its subsequent realization or on the basis of microprocessor means, or programmed means of creation of digital techniques (SPLD, CPLD, FPGA, SoC, SoPC).